Treatment of rats with hypolipidemic compound pirinixic acid protects their hearts against ischemic injury: are mitochondrial K(ATP) channels and reactive oxygen species involved - Nemčeková, Mária; Čarnická, Slávka; Ferko, Miroslav; Muráriková, M; Ledvényiová, V; Ravingerová, Táňa (Physiological research, 2013)
Hypolipidemic compound pirinixic acid (WY-14643, WY) is known to exert pleiotropic (other than primary) effects, such as activation of peroxisome proliferator-activated receptors (PPAR-alpha), transcription factors regulating different cardiac functions. Their role in ischemia-reperfusion (I/R) injury and cardioprotection is less clear, although protective effects of PPAR agonists have been documented. This study was designed to explore the effects of WY on the I/R injury in the rat heart and potential mechanisms involved, including mitochondrial K(ATP) channels (mitoK(ATP)) opening and production of reactive oxygen species (ROS). Langendorff-perfused hearts of rats intragastrally treated with WY (3 mg/kg/day) for 5 days and of control animals were subjected to 30-min global ischemia and 2-h reperfusion with or without 15-min perfusion with mitoK(ATP) blocker 5-hydroxydecanoate (5-HD) prior to I/R. Evaluation of the infarct size (IS, TTC staining) served as the main end-point of protection. Lipid peroxidation (a marker of ROS production) was determined by measurement of myocardial concentration of conjugated dienes (CD), whereas protein expression of endothelial NO synthase was analysed by Western blotting. A 2-fold increase in the cardiac protein levels of eNOS after treatment with WY was accompanied by lower post-I/R levels of CD compared with those in the hearts of untreated controls, although WY itself enhanced ROS generation prior to ischemia. IS was reduced by 47 % in the hearts of WY-treated rats (P<0.05), and this effect was reversed by 5-HD. Results suggest that PPAR-alpha activation may confer protection against lethal I/R injury in the rat heart that involves up-regulation of eNOS, mitoK(ATP) opening and reduced oxidative stress during I/R.
Keywords: Myocardial Reperfusion Injury; funkce levé komory srdeční; kardiotonika; reaktivní formy kyslíku; PPAR alpha; Cytoprotection; Potassium Channels; peroxidace lipidů; perfuze; draslíkové kanály; Oxidative Stress; Potassium Channel Blockers; PPAR alfa; krysa rodu Rattus; infarkt myokardu; pyrimidiny; Ventricular Function, Left; kontrakce myokardu; Myocardial Infarction; potkani Wistar; myokard; Disease Models, Animal; Rats, Wistar; reperfuzní poškození myokardu; mužské pohlaví; zvířata; hypolipidemika; cytoprotekce; synthasa oxidu dusnatého, typ III; Time Factors; Hypolipidemic Agents; Myocardium; oxidační stres; Rats; Animals; Perfusion; Reactive Oxygen Species; Cardiotonic Agents; časové faktory; blokátory draslíkových kanálů; Male; modely nemocí na zvířatech; Myocardial Contraction; Nitric Oxide Synthase Type III; Pyrimidines; Lipid Peroxidation